Evaluasi Efisiensi Anggaran Proyek Peningkatan Jalan Provinsi: Studi Kasus Ruas Parsoburan-Borbor-Janji Maria - Silaen, Joshua Riski; Sobirin , Mohamad (Syntax Corporation, 2025)
Budget efficiency is a crucial aspect in road infrastructure project management. This study analyzes budget efficiency in the provincial road improvement project on the Parsoburan-Borbor-Pangururan-Janji Maria route in Toba Regency, North Sumatra, with a contract value of IDR 5,784,624,000. The research aims to evaluate project budget efficiency and identify factors that influence it quantitatively. The research method uses a quantitative approach with a cross-sectional design involving 45 respondents. The results show that the budget efficiency level reaches 99.5% (fairly efficient category). Correlation tests show significant relationships between planning quality (r=0.762; p<0.001), procurement management (r=0.684; p<0.001), and HR competence (r=0.591; p<0.01) with budget efficiency. Regression analysis shows the model can explain 73.4% of budget efficiency variation (R²=0.734). Planning quality factor provides the largest contribution (β=0.451; p<0.001).